Influence of the eluent in the MIL-53(Al) selectivity for xylene isomers separation - Mariana A. Moreira (2011)
Metal-organic framework MIL-53 (Al) pellets were tested for selective adsorption and separation of xylene isomers with the aim of studying the influence of the solvent used at bulk concentrations. In this way, a set of single and multicomponent pulse experiments to measure selectivities was conducted, with iso-octane, n-hexane, and n-heptane as eluents, at 313 K. In order to complete this study, multicomponent breakthrough experiments were also performed, under the same conditions, in the presence of these three eluents, and the obtained selectivities were compared. MIL-53(Al) presented a preference for o-xylene over m-xylene and p-xylene in all experiments. The selectivity was higher when n-heptane was the eluent. For the breakthrough experiments that used n-heptane as the eluent, selectivities of 2.1 were obtained for o-xylene over m-xylene and over p-xylene. It was possible to conclude that the choice of eluent influences the adsorption selectivity and capacity of the adsorbent. This could result, among other factors, from the adsorbent adsorbate interactions. These interactions may also occur with the eluent molecules (as an adsorbate), which influences the adsorption capacity.